Novel Technological and Management Options for Accelerating Transformational Changes in Rice and Livestock Systems - Chirinda, Ngonidzashe; Arenas Calle, Laura N.; Loaiza, Sandra; Trujillo, Catalina; Katto, María Cristina; Chaparro, Paula; Nunez, Jonathan; Arango, Jacobo; Martínez Barón, Deissy; Loboguerrero Rodriguez, Ana María; Becerra López Lavelle, Luis Augusto; Ávila, Ivan; et al. (MDPI, 2017)
Agricultural producers grapple with low farm yields and declining ecosystem services within their landscapes. In several instances, agricultural production systems may be considered largely unsustainable in socioeconomic and ecological (resource conservation and use and impact on nature) terms. Novel technological and management options that can serve as vehicles to promote the provision of multiple benefits, including the improvement of smallholder livelihoods, are needed. We call for a paradigm shift to allow designing and implementing agricultural systems that are not only efficient (serving as a means to promote development based on the concept of creating more goods and services while using fewer resources and creating less waste) but can also be considered synergistic (symbiotic relationship between socio-ecological systems) by simultaneously contributing to major objectives of economic, ecological, and social (equity) improvement of agro-ecosystems. These transformations require strategic approaches that are supported by participatory system-level research, experimentation, and innovation. Using data from several studies, we here provide evidence for technological and management options that could be optimized, promoted, and adopted to enable agricultural systems to be efficient, effective, and, indeed, sustainable. Specifically, we present results from a study conducted in Colombia, which demonstrated that, in rice systems, improved water management practices such as Alternate Wetting and Drying (AWD) reduce methane emissions (~70%). We also show how women can play a key role in AWD adoption. For livestock systems, we present in vitro evidence showing that the use of alternative feed options such as cassava leaves contributes to livestock feed supplementation and could represent a cost-effective approach for reducing enteric methane emissions (22% to 55%). We argue that to design and benefit from sustainable agricultural systems, there is a need for better targeting of interventions that are co-designed, co-evaluated, and co-promoted, with farmers as allies of transformational change (as done in the climate-smart villages), not as recipients of external knowledge. Moreover, for inclusive sustainability that harnesses existing knowledge and influences decision-making processes across scales, there is a need for constant, efficient, effective, and real trans-disciplinary communication and collaboration.